Intuition in medicine: enhancing the practice of good clinical reasoning - Laura Leondina-Campanozzi (Bioethics Update)
Background: Intuitions play an important role in clinical reasoning that is particularly significant in the intellectual process of diagnostic hypothesis generation. Gaining insights in its theoretical underpinnings is a way to enhance the understanding and use of clinical intuition, consistent with its importance in medicine. Objectives: After underscoring the pivotal function of clinical intuitions, the article investigates its defining traits, through an overview of the main philosophical perspectives and illustrative references from the field of science and medicine. Methods: The Platonic tradition is integrated with the Aristotelian-Thomistic one to provide a more comprehensive and realistic picture of intuition in medical practice. Results-Conclusions: The view of clinical intuition as a form of intellectual faculty whose subject matter is the particular represents a preliminary step toward future research aimed at identifying those dynamic conditions that can foster the trigger of good intuitions.